Effects of antidepressants on serum concentrations of bone metabolism markers and major electrolytes in patients from routine psychiatric practice - Riznić, Nikola; Milovanović, Dragan R.; Djukić Dejanović, Slavica; Janković, Slobodan M.; Ravanić, Dragan; Ignjatović Ristić, Dragana; Petrović, Dušan; Jovanović, Mirjana; Mladenović, Violeta; Ružić Zečević, Dejana; Janjić, Vladimir (Vojnosanitetski pregled, 2017)
Background/Aim. Data about effects of antidepressant on calcium, phosphorous and magnesium metabolisms are very scorce. The aim of this study was to investigate effects of antidepressants on serum concentration of bone metabolism markers and main electrolytes in patients from routine psychiatric practice. Methods. A prospective, before-and-after, time-series research included 9 males and 24 females, with average 53.3 ± 11.5 years-of-age, suffering from depression (n = 26) and neurotic disorders (n = 7), mostly taking selective serotonin reuptake inhibitors. We measured analytes at baseline, and 4th, 6th and 12th weeks during the treatment and tested the parameter changes from baseline and the trends with appropriate statistics at p ≤ 0.05 significance level. Results. The age above 60 years was a significant factor for appearance of negative cumulative changes (in percent) of 25-hydroxyvitamin D – 25(OH)D concentrations from the baseline (OR = 11.4, 95% CI 1.2–113.1, p = 0.037). Serum concentrations of calcium significantly correlated with sodium (rs = 0.531, p < 0.001), with chloride (r = 0.496, p < 0.001), with magnesium (rs = 0.402, p < 0.001) and with osteocalcin (r = 0.240, p = 0.019). Significant correlations were among phosphorous with chloride (r = -0.218, p = 0.035); magnesium with sodium (r = 0.295, p = 0.004) and with potassium, (r = 0.273, p = 0.009); osteocalcin with C-telopeptide (r = 0.760, p < 0.001) with sodium (r = 0.215, p = 0.039) and with chloride (r = 0.209, p = 0.041); sodium with chloride (r = 0.722, p < 0.001). There were no statistically significant changes between antidepressant treatment and changes of absolute serum concentration of calcium, magnesium, phosphorous, 25(OH)D, osteocalcin, C-telopeptide, sodium, potassium and chloride. There were no statistically significant changes in frequency of disturbances in values of laboratory analytes (below/above lower/upper normal limits), too. Conclusion. Antidepressant treatment was not significantly associated with the changes in study analytes but some of them positively correlated with each other, suggesting the need for individual patient approach and further research in the field of bone metabolism in patients with mental disorders.